2021
DOI: 10.1021/acsaem.1c00664
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Li Electrodeposition Behavior through Mesoporous Silica Thin Film in Anode-Free Lithium Metal Batteries

Abstract: Lithium metal anode material suffers from the formation of a dendritic structure and manufacturing difficulties in Li metal batteries. Although anode-free lithium metal batteries (AFLMBs) have received broad interest due to their high energy density and easy fabrication, controlling the morphology of electrodeposited Li is challenging. In this work, we report on the use of mesoporous silica thin films (MSTFs) with perpendicular nanochannel (pore size ∼6 nm) stacking on a stainless steel (SS) substrate as the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…The accumulation of dead Li causes rapid capacity fade of the cell. 18 Thus, many different strategies have been developed to improve the uniformity of lithium deposition on heterogeneous substrates in AFLMBs, where all the active lithium is provided by the cathode, including electrolyte additives, 11,[19][20][21][22][23][24] surface modication of the current collector, [25][26][27][28][29][30] and articial SEI. [31][32][33] Among them, one effective approach is to increase the surface lithiophilicity of the copper current collector by uniformly constructing a lithiophilic layer, which provides abundant nucleation sites by enhancing the affinity of lithium.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of dead Li causes rapid capacity fade of the cell. 18 Thus, many different strategies have been developed to improve the uniformity of lithium deposition on heterogeneous substrates in AFLMBs, where all the active lithium is provided by the cathode, including electrolyte additives, 11,[19][20][21][22][23][24] surface modication of the current collector, [25][26][27][28][29][30] and articial SEI. [31][32][33] Among them, one effective approach is to increase the surface lithiophilicity of the copper current collector by uniformly constructing a lithiophilic layer, which provides abundant nucleation sites by enhancing the affinity of lithium.…”
Section: Introductionmentioning
confidence: 99%
“…A home‐built online GC system (Agilent 7890) with a pulsed discharge helium ionization detector was used to analyze the gas products. [ 56,57 ] Since each GC measurement required 30 min, the released gases were accumulated in the cell for 30 min during the charge–discharge process prior to the GC measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Lo et al reported the use of mesoporous silica thin films (MSTF) with vertical nanochannels stacked on stainless steel (SS) substrates to improve the battery performance. [104] The MSTF composite layer consists of a continuous mesoporous silica film, ≈30 nm thick, possessing negatively charged uniform perpendicular nanochannels (6.5 ± 0.3 nm), which makes it electrically insulating and has good lithium affinity. The porous MSTF regulates the lithium electrodeposition process by the microcrystalline structure, allowing lithium deposition on the Li (110) surface with the activation energy of only 0.01 eV, which is even lower than the LiAg alloy.…”
Section: Modification Of the Interfacementioning
confidence: 99%
“…d) Schematic illustrations of the Li electrodeposition process on the SS and MSTF⊥SS in the anode-free Li metal batteries. Reproduced with permission [104]. Copyright 2021, American Chemical Society.…”
mentioning
confidence: 99%